THE INFLUENCE OF THE COVID-19 PANDEMIC ON THE SELF-CONFIDENCE OF CLINICAL CLERKSHIP STUDENTS, FACULTY OF MEDICINE, NUSA CENDANA UNIVERSITY - Sulla, Paula Beatric Alexis; Dedy, Maria Agnes Etty; Damanik, Efrisca Meliyuita Br; Sagita, Sidarta (Cendana Medical Journal, 2022)
Background: COVID-19 first appeared in Wuhan Province, China in 2019 to the extent that it spread worldwide including Indonesia. COVID-19 cases have declined but vaccine targets have not been fully met, and the number of health workers who died during the COVID-19 pandemic has been one of the things that impact the confidence level of the clinical clerkship students. Objective: This study aims to identify the effect of the COVID-19 pandemic on the confidence of clinical clesrkship students at the faculty of medicine, Nusa Cendana University. Methods: The research was conducted analytically observational with a cross sectional approach conducted on 88 respondents of the Faculty of Medicine of Nusa Cendana University using google form. Sampling is performed using stratified random sampling techniques. This study was analyzed univariate and bivariate using Linear Regression tests. Result: Out of 88 respondents, 83 (94.3%) agreed to have sufficient confidence, 4 respondents (4.5%) strongly agreed to have sufficient confidence, and 1 respondent (1.1%) did not agree to have sufficient confidence. Meanwhile, 87 people (98,9%) were concerned about the pandemic of COVID-19 and 1 person (1,1%) who were not concerned about the pandemic of COVID-19 with the results of the bivariate analysis of both variables were obtained a p= 0,070. Conclusion: There was no significant effect from the COVID-19 pandemic on the confidence of clinical clesrkship students at the faculty of medicine, Nusa Cendana University.